'Welcome to Europe': A Bridge East of Architectural History. Issue 1 (13th June 2018) - Kılınç, Kıvanç
Abstract : This position paper examines the complex boundaries that separate Europe from both its constructed margins and those of its imagined Others. Where exactly do we enter the Continent and where does it end? Is it while crossing the world-famous bridge on the Bosporus, for instance, that one receives the first impression of Europe, or is it somewhere farther west — past a 'wall' protected by a strong border regime? To address these questions, this paper tells two concomitant stories about the practices of urban governance and architectural design in Turkey in the early twentieth century by providing snapshots of numerous encounters and negotiations between multiple actors: American public health specialists, European-trained local bureaucrats, and a French city planner. While Turkey's dubious position between the West and the East provides the potential for rethinking the boundaries of the Continent, the paper uses the Turkish case primarily to unpack the idea of 'Europe' as both a fluid entity and a fixed location, an uneven terrain upon which canonical discourses of identity are constructed. In doing so, it points to the interchangeability of subject positions, which often result in competing narratives of modernization, urban design, and the whereabouts of the line separating Turkey from Europe.